A novel modified thaw‐siphon method for extracting cryoprecipitate: The Bokutoh‐siphon method. Issue 4 (26th February 2021) - Nishimura, Shigeko; Teratani, Miyuki; Igarashi, Tomoko; Nakahara, Michiyo; Hazama, Yuki; Ohtani, Sae; Fujita, Hiroshi
Abstract: Background: Cryoprecipitate (CRYO) is neither produced nor supplied by the Japanese Red Cross Society. A novel CRYO extraction method established in‐house by modifying a thaw‐siphon technique was demonstrated in this study. Study Design and Methods: A pack of fresh frozen plasma was thawed and equally divided into two bags for CRYO extraction by different methods. CRYO was extracted from the blood plasma using a standard centrifugation method and our modified thaw‐siphon method (Bokutoh‐siphon method; B method). The two different CRYOs extracted were analyzed to compare the differences in the amount of fibrinogen recovered, clotting factors extracted, and clotting activity. Results: The amount of fibrinogen in the CRYO extracted using the B‐siphon method was similar to that obtained using the standard method (recovery of fibrinogen: B‐siphon method: 71.2% vs. standard method: 61.0%). The amount of clotting XIII factor extracted using the B‐siphon method was significantly lower than those extracted using the standard method. On the other hand, clotting II, V factors, and C1q esterase inhibitor not concentrated in CRYO content from the B‐siphon method were significantly higher than that from the standard method. Conclusion: A new in‐house CRYO preparation method was established by modifying a previously used thaw‐siphon method. A coagulation factor‐rich CRYO was extracted from plasma frozen at −40°C along with the first fraction of thawed plasma, without using a large‐capacity refrigerated centrifuge for blood bags.